New York : The monocle travel guide series - Monocle, ....- (Berlin : Gestalten, 2020)
New York has been photographed and filmed a million times. It’s depicted as a place of constant hustle and no-nonsense residents; of endless commerce and impossibly tall buildings. The purpose of this travel guide is to cut through all the imagery and offer you some inside knowledge. Our team of editors and correspondents have put together a list of the finest venues and experiences that the Big Apple has to offer.
Keywords: reisgids